Pedagogical work, stress regulation and work-related well-being among early childhood professionals in integrated special day-care groups. Issue 1 (2nd January 2016) - Nislin, Mari A.; Sajaniemi, Nina K.; Sims, Margaret; Suhonen, Eira; Maldonado Montero, Enrique F.; Hirvonen, Ari; Hyttinen, Sirpa
Abstract: The aim of this study was to investigate the relationship between early childhood professionals' (ECPs) stress regulation (using salivary cortisol and alpha-amylase [AA] measurements), work engagement and the quality of their pedagogical work in integrated special day-care groups. Participants were 89 ECPs from 21 integrated special day-care groups located in Helsinki, Finland. The special educational needs of children (who were between 3 and 6 years of age) in these groups varied from language disorders and self-regulation difficulties to severe disabilities. Data was collected by using work engagement surveys, salivary cortisol and AA measurements and observational assessments of pedagogical work. This study is novel, in that it combines approaches from different disciplines to investigate work-related well-being among ECPs. Our findings demonstrate the close relationship between ECPs' stress regulation and the quality of pedagogical work in teams. Whilst ECPs' high work engagement was associated with better-quality pedagogical work, we did not find any associations between different biomarkers and work engagement. Our study highlights the importance of teamwork, not only as fundamental to high-quality early childhood special education, but also in supporting the well-being of ECE professionals. The findings can be applied in future studies and can be used to inform intervention aiming to enhance working conditions in day-care centres.